Doing Development Differently at Scale - Pellini, Arnaldo; Karetji, Petrarca C.; Soekadis, Ade (Knowledge, Politics and Policymaking in Indonesia, 2018)
In recent decades there has been an increasing recognition that politi cs and political institutions matter for development. There is also a much greater interest in contextually grounded approaches. This has st emmed from an acknowledgement that purely technocratic approaches to d evelopment often result in failure because they do not take into accou nt the nature of political institutions. Nor do they take account of t he context in a particular developing country and the interests and in centives of powerful national actors. Policy processes are embedded in specific social, political and organisational contexts. Approaches th at focus on implementing universal best practices in evidence-informed policymaking are unlikely to be successful. Instead, what is needed i s an approach that takes the local context as the starting point for u nderstanding what issues are relevant to policymakers and developing c ontextually appropriate solutions. The authors of this chapter reflect on the management approaches and systems that may be required to enab le and support large-scale development programmes to be flexible and a daptive to the local policy context and circumstances. The chapter arg ues that such programmes struggle to adopt adaptive management princip le and that to do that at scale requires some changes in the way such programmes are managed.
Keywords: Adaptive Management; Doing development differently; Evidence-informed policymaking; Indonesia; Knowledge sector; Thinking and working politically